NURSING MANAGEMENT: A LOOK FROM THE PERSPECTIVE OF COMPLEX THINKING - Cristiano Caveião; Ana Paula Hey; Juliana Helena Montezeli (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976927176 Objective: to reflect on the interface of Complex Thinking proposed by Morin in pedagogical practice in the teaching of Nursing Administration. Method: article of reflection, where the authors were based their experiences as teachers in the area of nursing administration in educational institutions; questioning the pedagogical practice, discussing issues related to the daily work of teachers, in light of complex thinking. Results: being managing a subprocess within this profession, the great challenge of teaching this discipline is distancing it from a dichotomous practice that considers care and management, elements watertight. Final Thoughts: to bring about changes in the management and nursing care with creativity and autonomy, it is necessary to rethink the training, with regard to the organization of the learning process. This way, you can contribute to the formation of critical and questioning individuals; glimpsing multidimensionalizar to think, ie, taking the complexity premised.